Studies on comparative anatomy of endangered plant Changium smyrnioides Wolff - QIU Ying-xiong; FU Cheng-xin (浙江大学学报. 农业与生命科学版)
With age adding, the area ratio of phloem and xylem decreases in Ch. smyrnioides. Differentiation of vascular cambium is active in 34 years root. The vascular bundle of stem is the type of double phloem. The anther is tetrasporangiate. Simultaneous cytokinesis in the microspore mother cell follows meriosis. The species is suspended placentation, anatropous ovule and nuclear endosporm. The embryo of Ch. smyrnioides is very small in mature seeds. They could successfully germination after 4-6 months of afterripening. The incoordination between the afterripening of seed and the raining season of East China may be one of the endangered reasons in Ch. smyrnioides.